P38 Mitogen-activated protein kinase is stimulated by both angiotensin II and angiotensin III in cultured rat astrocytes. (June 2014) - Z. Alanazi, Ahmed; Patel, Paras; Clark, Michelle A.
Abstract Context: Previously we showed that angiotensin (Ang) II and Ang III induced phosphorylation of ERK1/2 and JNK mitogen-activated protein (MAP) kinases in rat astrocytes. Objectives: To determine whether these peptides induce p38 MAP kinase in astrocytes. Materials and methods: We used brainstem astrocytes as a model system to determine whether Ang II and Ang III induce p38 MAP kinase protein phosphorylation. Results: Treatment of astrocytes with increasing concentrations of both peptides caused a dose-dependent increase in p38 MAP kinase phosphorylation. The effect of Ang II and Ang III was maximal at 10 nM and 100 nM concentrations, respectively. The effects of the peptides were rapid occurring within minutes of treatment. There was a significant difference in the ability of the peptides to induce p38 MAP kinase phosphorylation. The ability of Ang II to induce p38 MAP kinase was almost twice than that of Ang III, suggesting that Ang II was more potent than Ang III in this effect. Ang AT1 receptor mediated the actions of the peptides since pretreatment with losartan prevented p38 MAP kinase phosphorylation by Ang II and Ang III. In addition, blockade of Ang II metabolism to Ang III with the aminopeptidase A inhibitor glutamate phosphonate was ineffective in ameliorating Ang II phosphorylation of p38 MAP kinase, suggesting that Ang II directly stimulated p38 MAP kinase phosphorylation. Conclusion: These findings provide insight into the molecular nature of the actions of these peptides and offer a possible mechanism by which these Ang peptides physiological and possibly pathological actions occur in astrocytes.